Malignant retroperitoneal paraganglioma treated with radiotherapy: A case report - Ghammad, Sanae; Chebihi Hassani, Ghita; Allouche, Fadwa; Alami, Zineb; Bouhafa, Touria; Hassouni, Khalid (Journal of Surgery and Medicine, 2019)
Paragangliomas are rare tumors arising from undifferentiated cells of the primitive neural crest. We report a case of a 33-year-old female patient who presented a large firm retroperitoneal tumor situated on the left flank above the left kidney. Levels of the serum epinephrine and norepinephrine were high. We performed a scanned biopsy; the histopathological examination and the immunohistochemical analyses concluded the diagnosis of a retroperitoneal paraganglioma. The tumor was judged secreting and inoperable; therefore it was decided to be treated with radiotherapy.